2021
DOI: 10.1016/j.ijbiomac.2021.01.206
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the disordered domain structure of MeCP2 on its structural stability and dsDNA interaction

Abstract: Methyl-CpG binding protein 2 (MeCP2) is a transcriptional regulator and a chromatin-associated structural protein. MeCP2 deregulation results in two neurodevelopmental disorders: MeCP2 dysfunction is associated with Rett syndrome, while excess of activity is associated with MeCP2 duplication syndrome. MeCP2 is an intrinsically disordered protein (IDP) constituted by six structural domains with variable, small percentage of well-defined secondary structure. Two domains, methyl-CpG binding domain (MBD) and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…MeCP2 is an intrinsically disordered protein 32,33 . Characteristically, these proteins lack a stable three-dimensional structure and interact electrostatically with DNA and other proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MeCP2 is an intrinsically disordered protein 32,33 . Characteristically, these proteins lack a stable three-dimensional structure and interact electrostatically with DNA and other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In MeCP2 only the MBD is structured, while the ID and TRD are structurally disordered but form a secondary structure upon binding interaction partners and/or DNA 1,34 . We postulated an electrostatic interaction between the ID-TRD and LEDGF which is often the case for structurally disordered proteins 32,33 . Three positively charged regions are present in the TRD and we mutated the four or five positively charged residues to alanines (Figure 5A).…”
Section: Characterization Of the Mecp2-ledgf Interactionmentioning
confidence: 99%
“…The first identified MBD protein, MeCP2, is partially disordered, multifunctional and consists of six domains. The MBD-flanking domains (NTD and ID) are completely disordered and can alter the structure and function of the MBD domain [39]. Soybean GmMBD10c protein belongs to the class 1 MBD protein family and contains a high ratio of disorder-promoting amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that both NTD and ID increase the intrinsic structural stability of MBD, as observed by thermal unfolding experiments: at pH 7, the unfolding temperature T m is 38.4 • C and 46.2 • C for MBD and NTD-MBD-ID, respectively, and the unfolding enthalpy ∆H m is 38 kcal/mol and 46 kcal/mol for MBD and NTD-MBD-ID, respectively [34]. All other domains also have a minor stabilizing effect on MBD [35]. These unfolding experiments were undertaken by following the intrinsic fluorescence emission of the single tryptophan located at the MBD (W104), and consequently they accurately reflect the thermal stability of MBD.…”
Section: Introductionmentioning
confidence: 86%